Penerapan Problem Based Learning (PBL) dengan Pemberian Biografi Ilmuwan Pada Mata Kuliah Fisika Dasar I: Dampak Sikap Ilmiah dan Motivasi belajar - Hadma Yuliani (Kappa Journal, 2021)
The application of PBL along with the biographies of scientists in learning physics is expected to have an impact on scientific attitudes and student motivation to learn. The objectives of this study were: (1) To find out the improvement of students' scientific attitude after PBL was applied by giving scientists biographies in Basic Physics I course; (2) To find out the increase in students' learning motivation after PBL by applying the biographies of scientists in the Basic Physics I course. This study used a quantitative approach with descriptive research type. The data collection technique used a questionnaire for scientific attitudes and learning motivation. The results showed: (1) There was an increase in the ability of scientific attitudes by applying PBL by giving scientists biographies in the Basic Physics I course in the medium category with an N-gain value of 0.523 and (2) There was an increase in learning motivation by applying.